Iron and holotransferrin induce cAMP-dependent differentiation of Schwann cells - Salis, Carolina (2012)
The differentiation of myelin-forming Schwann cells (SC) is completed with the appearance of myelin proteins MBP and P0 and a concomitant downregulation of markers GFAP and p75NTR, which are expressed by immature and adult non-myelin-forming SC. We have previously demonstrated that holotransferrin (hTf) can prevent SC dedifferentiation in culture (Salis et al., 2002), while apotransferrin (aTf) cannot. As a consequence, we used pure cultured SC and submitted them to serum deprivation in order to promote dedifferentiation and evaluate the prodifferentiating ability of ferric ammonium citrate (FAC) through the expression of MBP, P0, p75NTR and c-myc. The levels of cAMP, CREB and p-CREB were also measured. Results show that Fe3+, either in its free form or as hTf, can prevent the dedifferentiation promoted by serum withdrawal. Both FAC and hTf were proven to promote differentiation, probably through the increase in cAMP levels and CREB phosphorylation, as well as levels of reactive oxygen species. This effect was inhibited by deferroxamine (Dfx, an iron chelator), H9 (a cAMP-PKA antagonist) and N-acetylcysteine (NAC, a powerful antioxidant).